Membumikan Teologi Lingkungan: Studi Implementasi Pemikiran Mujiyono Abdillah - Sulbi; Firdaus, Abdullah; Arifullah, Mohd; Asyrap Sanid ID, M; Tazkaa, Mu'tazzah; Cahya, Eka; Nursaktila, Nia (Kartika: Jurnal Studi Keislaman, 2025)
Environmental issues in Tanjungpinang City, such as the scarcity of green open spaces, increasing waste volume, and pollution, indicate the need for an approach that is not only structural but also addresses the cultural and spiritual aspects of the community. This journal examines the implementation of Mujiyono Abdillah's environmental theological thought as a response to this ecological awareness crisis. The research aims to analyze how Mujiyono Abdillah's environmental theological thought is implemented in environmental management in Tanjungpinang City. Using a qualitative approach with a descriptive-analytical method, data was collected through field observations, in-depth interviews with religious leaders, environmental activists, and government officials, as well as documentation of environmental policies and programs. Data analysis was carried out through data reduction, data presentation, and conclusion. The research results show that the application of Mujiyono Abdillah's environmental theological values, including the concepts of al-'ālamīn (the universe), al-samā' (the sky), al-ardh (the earth), and al-bī'ah (the environment), is still limited in Tanjungpinang City. This research emphasizes the importance of a faith-based and spiritual approach in sustainable environmental management, offering a practical framework for integrating ecological piety into education, policy, and community culture.